The role of facial appearance on CEO selection after firm misconduct - GOMULYA, David M. (Institutional Knowledge at Singapore Management University, 2017)
We investigate a particular aspect of CEO successor trustworthiness that may be critically important after a firm has engaged in financial misconduct. Specifically, drawing on prior research that suggests that facial appearance is one critical way in which trustworthiness is signaled, we argue that leaders who convey integrity, a component of trustworthiness, will be more likely to be selected as successors after financial restatement. We predict that such appointments garner more positive reactions by external observers such as investment analysts and the media because these CEOs are perceived as having greater integrity. In an archival study of firms that have announced financial restatements, we find support for our predictions. These findings have implications for research on CEO succession, leadership selection, facial appearance, and firm misconduct.